2018
DOI: 10.1016/j.bbamcr.2018.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in paracellular permeability and chemosensitivity to doxorubicin by claudin-1 in spheroid culture models of human lung adenocarcinoma A549 cells

Abstract: Chemotherapy resistance is a major problem in the treatment of cancer, but the underlying mechanisms are not fully understood. We found that the expression levels of claudin-1 (CLDN1) and 3, tight junctional proteins, are upregulated in cisplatin (CDDP)-resistant human lung adenocarcinoma A549 (A549R) cells. A549R cells showed cross-resistance to doxorubicin (DXR). Here, the expression mechanism and function of CLDN1 and 3 were examined. CLDN1 and 3 were mainly localized at tight junctions concomitant with zon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 38 publications
1
46
0
Order By: Relevance
“…OCLN may be not directly implicated in the acquisition of resistance to anticancer drugs in lung adenocarcinoma cells, but it suppresses chemosensitivity in spheroid cells. Our recent data indicate that CLDN1 and CLDN2 are also implicated in the development of chemoresistance in 3D spheroid cells 8 , 9 . These tight junctional proteins may be new targets of adjuvant chemotherapy in lung adenocarcinoma.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…OCLN may be not directly implicated in the acquisition of resistance to anticancer drugs in lung adenocarcinoma cells, but it suppresses chemosensitivity in spheroid cells. Our recent data indicate that CLDN1 and CLDN2 are also implicated in the development of chemoresistance in 3D spheroid cells 8 , 9 . These tight junctional proteins may be new targets of adjuvant chemotherapy in lung adenocarcinoma.…”
Section: Discussionmentioning
confidence: 88%
“…These results suggest that OCLN may not be essential to regulate paracellular permeability to ions, but we cannot deny the involvement of other CLDNs. Actually, the expression of CLDN1 was also elevated by CDDP-resistance in A549 cells, which was blocked by LY-294002 9 . The balance of the expression of CLDNs and OCLN may induce this property of paracellular permeability to ions.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Cells were cultured on transwell plates (0.4 µm pore size, 12 mm diameter) with polyester membrane inserts (Corning Incorporated, Corning, NY, USA). The barrier function of TJ was estimated by transepithelial electrical resistance (TER) and flux of doxorubicin [22,23].…”
Section: Paracellular Barrier Functionmentioning
confidence: 99%
“…Another study by a Japanese group of researchers reported a high expression of claudin-4 in the ovarian cancer tissues of platinum-resistant patients [99]. In lung cancer, claudin-1 is a key deciding factor for metastasis and a responsible factor for drug resistance towards cisplatin through the up-regulation of Unc-51 Like Autophagy Activating Kinase 1 (ULK1) phosphorylation [100,101]. It is also known to enhance drug resistance in liver cancer cells by modulating autophagy to achieve drug resistance.…”
Section: Claudins In Chemoresistancementioning
confidence: 99%